2018
DOI: 10.1016/j.jvs.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Home-Based Exercise Intervention of Wearable Technology and Telephone Coaching on Walking Performance in Peripheral Artery Disease: The HONOR Randomized Clinical Trial

Abstract: A total of 200 patients with peripheral arterial disease (PAD) were randomized to home-based exercise consisting of on-site sessions for the first month, active exercise, and coaching (99 patients) vs usual care (101 patients) for 9 months. The mean change in walking distance was better in the usual care group than in the exercise group. Conclusion:A home-based exercise program consisting of a wearable activity monitor and telephone coaching did not improve walking performance at 9-month follow-up. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(104 citation statements)
references
References 0 publications
1
102
0
1
Order By: Relevance
“…These sessions included discussion of objectively assessed or patient‐reported adherence to the walking programmes in all trials ( Table ). Recognized counselling methods, such as motivational interviewing or patient‐centred assessment and counselling for exercise, were employed in three trials. The motivational sessions included attending a limited number of group exercise sessions at a central location in some programmes ( Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These sessions included discussion of objectively assessed or patient‐reported adherence to the walking programmes in all trials ( Table ). Recognized counselling methods, such as motivational interviewing or patient‐centred assessment and counselling for exercise, were employed in three trials. The motivational sessions included attending a limited number of group exercise sessions at a central location in some programmes ( Table ).…”
Section: Resultsmentioning
confidence: 99%
“…All trials reported random allocation of patients to the intervention and control groups, although the method of random sequence generation was not reported in two trials. Only four trials reported blinding of the outcome assessors and only four reported sample size calculations. All but three trials reported that the analysis was by intention to treat.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 The recent HONOR trial, which evaluated an mHealth-augmented home-based exercise program for patients with PAD (in patients with a mean age of 70 years), also found no significant difference in significant adverse events between the intervention and control group. 58 While further research is needed into the safety of home-based CR programs, these results provide indirect support that they can be prescribed safely.…”
Section: Nontraditional Crmentioning
confidence: 96%